Cell-in-cell: a potential biomarker of prognosis and a novel mechanism of drug resistance in cancer - Liu, Xiaona; Yang, Jun (Frontiers in Oncology, 2023)
The cell-in-cell (CIC) phenomenon has received increasing attention over recent years because of its wide existence in multiple cancer tissues. The mechanism of CIC formation is considerably complex as it involves interactions between two cells. Although the molecular mechanisms of CIC formation have been extensively investigated, the process of CIC formation remains ambiguous. Currently, CIC is classified into four subtypes based on different cell types and inducing factors, and the underlying mechanisms for each subtype are distinct. Here, we investigated the subtypes of CIC and their major mechanisms involved in cancer development. To determine the clinical significance of CIC, we reviewed several clinical studies on CIC and found that CIC could serve as a diagnostic and prognostic biomarker. The implications of CIC on the clinical management of cancers also remain largely unknown. To clarify this aspect, in the present review, we highlight the findings of recent investigations on the causal link between CIC and cancer treatment. We also indicate the existing issues that need to be resolved urgently to provide a potential direction for future research on CIC.